Validation of the criteria matrix about the generalist's education in Dentistry Undergraduate Courses - Luiz Roberto Augusto NORO; Angelo Giuseppe Roncalli da Costa OLIVEIRA; Bruno César de Vasconcelos GURGEL; Pedro Henrique de ARAÚJO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The generalist training planned by Brazilian National Curriculum Guidelines for Dentistry undergraduate courses should provide actions for the development of health promotion in the field of public health, as well as disease prevention, diagnosis, planning, and dental treatment in the clinical field. Considering this complexity, the aim of the present study was to validate dimensions and sub-dimensions in dentistry training, allowing the identification of the main necessary competences and clinical skills for the generalist practice. For this, an evaluation study was carried out through the Delph's Method with the participation of 19 professors of Dentistry courses in Brazil working in the clinical area, considered "experts" in this theme. It was possible to identify clinical competences and skills in four dimensions and respective sub-dimensions: Transversal skills (biosafety, patient-team communication, humanization, ethical principles, dental documentation); Diagnosis and planning (diagnosis of dental caries, pulp and periapical changes, and periodontal diseases, clinical and imaging exam, and single treatment planning); Preventive activities (oral hygiene guidance and oral cancer prevention); and Dental care (anesthesia, basic oral surgery, drug prescription, subgingival scaling and root planing, dental restoration, minimally and non-invasive restoration treatment, and dental urgencies). The developed model represents a differentiated alternative for the construction of an innovative curriculum in Dentistry, aimed at the training of general practitioners to provide humanized, highly effective, and resolving care. The importance of clinical tutoring by professors on the essential clinical skills and abilities is highlighted in this study.